Principles and Practice of Cardiothoracic Surgery - Firstenberg, Michael S. (IntechOpen, 2013)
The field of cardiothoracic surgery continues to evolve at a rapidly expanding rate. New technologies are under constant development and as patients present with more advanced pathophysiology and complex comorbidities, management becomes more dependent on multi-disciplinary Teams. While there are a variety of innovative and high-profile topics that dominate the literature and the interests of clinicians, sometimes is it the basics both in terms of acute and sometimes unusual problems that often challenge cardiothoracic surgeons on a day to day basis. The goal of Principles and Practice of Cardiothoracic Surgery is to hopefully highlight the current state of the art management of these problems.